Smart Villagers as Actors of Digital Social Innovation in Rural Areas - Nicole Zerrer; Ariane Sept (Urban Planning, 2020)
Digital social innovation (DSI) is commonly associated with cities. However, DSI is not limited to urban space. In rural areas, it is the inhabitants themselves who start and push digitalization projects, and collaborate with professional actors from the outside. These innovators see digitalization as a chance to solve rural problems such as scarce mobility, declining community interactions, demographic change, or urban-rural digital divide. In consequence, DSI such as smart community centers, digitally managed car-sharing, or community apps also emerge in rural areas. The article seeks to better understand the different actors responsible for the rural digitalization processes. Based on interviews, document analyses, and field notes, the article focuses on two cases in rural Germany: Wesedun is part of a regional digitalization project empowering villagers to evolve own ideas, and Wokisrab shows off a bottom-up driven digitalization strategy. Both villages are aiming to improve the quality of life. Indicated by these cases and inspired by literature on social innovation, the actor groups are identified as drivers, supporters, and users. Based on the interactions and collaborations of these groups, we introduce Smart Villagers, the bottom-up actors of rural DSI. In order to design governance processes, the results indicate that even though Smart Villagers are motivated, skilled and engaged, they want and need the support of professional actors from the outside.
Keywords: 710; community building; digital social innovation; digitalization; elderly; ICT; rural areas; village development